Comparative TMT proteomic analysis unveils unique insights into Helicoverpa armigera (Hübner) resistance in Cajanus scarabaeoides (L.) Thouars - Ngugi-Dawit, A.; Njaci, Isaac; Higgins, T.J.V.; Williams, B.; Ghimire, Sita R.; Mundree, S.G.; Hoang, L.T.M. (MDPI, 2021)
Pigeonpea [Cajanus cajan (L.) Millspaugh] is an economically important legume playing a crucial role in the semi-arid tropics. Pigeonpea is susceptible to Helicoverpa armigera (Hübner), which causes devastating yield losses. This pest is developing resistance to many commercially available insecticides. Therefore, crop wild relatives of pigeonpea, are being considered as potential sources of genes to expand the genetic base of cultivated pigeonpea to improve traits such as host plant resistance to pests and pathogens. Quantitative proteomic analysis was conducted using the tandem mass tag platform to identify differentially abundant proteins between IBS 3471 and ICPL 87 tolerant accession and susceptible variety to H. armigera, respectively. Leaf proteome were analysed at the vegetative and flowering/podding growth stages. H. armigera tolerance in IBS 3471 appeared to be related to enhanced defence responses, such as changes in secondary metabolite precursors, antioxidants, and the phenylpropanoid pathway. The development of larvae fed on an artificial diet with IBS 3471 lyophilised leaves showed similar inhibition with those fed on an artificial diet with quercetin concentrations with 32 mg/25 g of artificial diet. DAB staining (3,3′-diaminobenzidine) revealed a rapid accumulation of reactive oxygen species in IBS 3471. We conclude that IBS 3471 is an ideal candidate for improving the genetic base of cultivated pigeonpea, including traits for host plant resistance.